2013
DOI: 10.1016/j.stem.2013.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Human Pluripotent State with Distinct Regulatory Circuitry that Resembles Preimplantation Epiblast

Abstract: Human embryonic stem cells (hESCs) are derived from the inner cell mass of the blastocyst. Despite sharing the common property of pluripotency, hESCs are notably distinct from epiblast cells of the preimplantation blastocyst. Here we use a combination of three small-molecule inhibitors to sustain hESCs in a LIF signaling-dependent hESC state (3iL hESCs) with elevated expression of NANOG and epiblast-enriched genes such as KLF4, DPPA3, and TBX3. Genome-wide transcriptome analysis confirms that the expression si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
383
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(409 citation statements)
references
References 58 publications
15
383
2
Order By: Relevance
“…4A). Gene ontology [18] enrichment analysis showed that the upregulated genes in naïve iPSCs were mainly involved in translation, embryonic development, and oxidative phosphorylation (Fig. 4D).…”
Section: Genome-wide Expression Analysis Of Patient-specific Naïve Ipscsmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). Gene ontology [18] enrichment analysis showed that the upregulated genes in naïve iPSCs were mainly involved in translation, embryonic development, and oxidative phosphorylation (Fig. 4D).…”
Section: Genome-wide Expression Analysis Of Patient-specific Naïve Ipscsmentioning
confidence: 99%
“…Previous studies have also suggested that human primed iPSCs and mouse EpiSCs can be converted to the naïve ground state via chemical manipulation or the overexpression of specific transcription factors [12][13][14][15][16][17]. Recently, several groups have further modified culture conditions to maintain human ESCs or iPSCs in the naïve ground state [12,13,15,18]. In particular, the 5i/L/FA system, developed by Jaenisch's group, contains a combination of inhibitors and growth factors sufficient for the induction and maintenance of the naïve ground state [15].…”
Section: Introductionmentioning
confidence: 99%
“…These conditions also make ES cell derivation possible from normally recalcitrant mouse strains [33] and rat embryos [34], and most recently a variant of 2i has been used to derive naive human ES cells [15][16][17]. In 2i conditions, ES cells are also heterogeneous and include a significant fraction of cells that can be prospectively isolated based on the expression of the extraembryonic transcription factor Hhex [35] (figure 1b).…”
Section: Totipotent Cellsmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that Tbx3 is involved in the developmental process by binding to the T-box motif with a 20-24 nucleotide palindromic sequence, the T-site, or half of the sequence in the promoters of target genes (5). A mutation of Tbx3 was demonstrated to be closely associated with the pluripotency of embryonic stem cells and the invasiveness of cancer (6). In resectable pancreatic carcinoma (7), melanoma (8), bladder cancer (9) and colorectal cancer (10), Tbx3 was revealed to be overexpressed and associated with poor prognosis of cancer.…”
Section: Introductionmentioning
confidence: 99%